ISLAM, HAM DAN KONSTITUSIONALISME INDONESIA - Taufiq Taufiq; Anik Kunantiyorini; Achmad Soeharto (LPPM Universitas Pekalongan, 2022)
The development of human rights as an intrinsic element that exists in humans has existed for a long time. Awareness of the existence of human rights, self-esteem, dignity and human dignity has actually been started since humans were on earth. This is because human rights have naturally existed since humans were born and are rights that are inherent and inseparable from human beings. The constitution in force in Indonesia recognizes that the position of human rights is very vital, although there are differences in terms of quality and quantity, especially in adopting human rights instruments, socio-political conditions which then have an influence on the contents of the constitution. Thus, it is clear that human rights are a basic need of society that must be contained in a constitution, as well as related to the basic values of the nation state itself.